Identification of novel biomass‐degrading enzymes from genomic dark matter: Populating genomic sequence space with functional annotation. Issue 8 (28th May 2014) - Piao, Hailan; Froula, Jeff; Du, Changbin; Kim, Tae‐Wan; Hawley, Erik R.; Bauer, Stefan; Wang, Zhong; Ivanova, Nathalia; Clark, Douglas S.; Klenk, Hans‐Peter; Hess, Matthias
ABSTRACT Although recent nucleotide sequencing technologies have significantly enhanced our understanding of microbial genomes, the function of ∼35% of genes identified in a genome currently remains unknown. To improve the understanding of microbial genomes and consequently of microbial processes it will be crucial to assign a function to this "genomic dark matter." Due to the urgent need for additional carbohydrate‐active enzymes for improved production of transportation fuels from lignocellulosic biomass, we screened the genomes of more than 5, 500 microorganisms for hypothetical proteins that are located in the proximity of already known cellulases. We identified, synthesized and expressed a total of 17 putative cellulase genes with insufficient sequence similarity to currently known cellulases to be identified as such using traditional sequence annotation techniques that rely on significant sequence similarity. The recombinant proteins of the newly identified putative cellulases were subjected to enzymatic activity assays to verify their hydrolytic activity towards cellulose and lignocellulosic biomass. Eleven (65%) of the tested enzymes had significant activity towards at least one of the substrates. This high success rate highlights that a gene context‐based approach can be used to assign function to genes that are otherwise categorized as "genomic dark matter" and to identify biomass‐degrading enzymes that have little sequence similarity to already known cellulases. The ability to assign function to genes that have no related sequence representatives with functional annotation will be important to enhance our understanding of microbial processes and to identify microbial proteins for a wide range of applications. Biotechnol. Bioeng. 2014;111: 1550–1565. © 2014 Wiley Periodicals, Inc.